Diseño y validación de un cuestionario para evaluar la competencia emocional - Arias Sáciga, July Mirtha (2022)
This article aims to show the process of design and validation of a questionnaire that collects information on the level of achievement of emotional competence in children, based on a qualitative and quantitative analysis. The construction, validity and reliability of the Emotional Competence Self-Assessment Questionnaire for children is presented, which evaluates five dimensions: emotional awareness, emotional regulation, emotional autonomy, socio-emotional skills, and life skills and well-being. The construction of the instrument has considered the following processes: conceptual and operational definition of the construct, preparation of the items, analysis of content validity through expert judgment, analysis of reliability of the instrument. The results show satisfactory evidence in relation to content validity and reliability, which makes it a valuable tool to be used by various researchers.